An enhanced procedure for mobile ipv6 route optimization to reduce handover delay and signaling overhead - Shah, P.A. (Springer Verlag, 2013)
Mobile IPv6 was proposed to provide mobility support to IPv6 based mobile nodes for continuous communication when they roam across different networks. As mobile nodes are dependent on a central entity home agent, hence due to mobility the path from mobile node to correspondent node via the home agent might be longer as compared to the direct path between them and results in triangular routing. Route Optimization in Mobile IPv6 using Return Routability provides the opportunity to eliminate the inefficient triangular routing between mobile and corresponding nodes and therefore, greatly improves the network performance. However, this Return Routability based route optimization involves the verification of mobile nodeâs reachability at home address and at care-of address (home test and care-of test) that results in higher handover delays and signalling overhead. This article presents an enhanced procedure for Mobile IPv6 Route Optimization that uses the concepts of shared secret Token and one time password along-with verification of mobile node via direct communication. The new solution was implemented in NS-2 making changes in the implementation of Mobile IPv6. Results show that the new solution provides lower handover delays and signalling overhead in comparison to the Return Routability based Mobile IPv6. Â© Springer International Publishing Switzerland 2014.